The G-translativity of Abel-type Transformations - Lemma, Mulatu (Sarajevo Journal of Mathematics, 2024)
Suppose 0<t_n<1 and _n→∞ t_n=1, then the Abel-type matrix, denoted by A_α,t, is the matrix defined by \[ a_nk=(k+αk)t^k_n(1-t_n)^α+1,α>-1. \] Recently the author proved that the Abel-type matrix A_α,t is -translative [2]. In this paper, we investigate the G-translativity of these transformations. 2000 Mathematics Subject Classification. 40A05, 40D99, 40C05